Digital Transgressions: Fiction and Change in the Era of Technological Expansion - Gordić Petković, Vladislava S. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Although the challenges that authors have had to face in their attempts to articulate their intimate and public (hi)stories happen to be much older than computers, it was digital technology that offered a miraculously effective existential and fictional frame for the mediation of literary testimonies. The fictional realism of the digital age is constructed around a newly formed class of young or middle-aged individuals most willing to adapt to a technology-centred civilisation and to a seismic technological change. The paper focuses on various forms of digital existence in contemporary fiction writing with the intention to illustrate crucial changes in the concept of reality and writers’ concern with the fidelity to experience. The surge of the so-called digital realism coincides with the revelation that the otherwise thin line between our digital personas and our real-world selves has grown obscure and even more difficult to detect, while new technologies are required to go beyond what our human senses can encompass and deliver. The paper intends to examine the ways new digital technologies contribute to representations of reality in the novels by Amber Tamblyn, Tamara Jecić, Mihajlo Spasojević and Aleksandar Ilić, all of them aspiring authors whose novels deal with ways of life amid social networks and digital technologies. Stalking friends and foes on Facebook and Instagram, starting relationships online and pursuing boundless obsession with multiplicity of identity are among complex issues these novels deal with, capturing the voices at the margins and letting the characters transcend their real-life grounded identities. The novels show that the gap dividing the virtual and the (corpo)real world narrows, as their narratives range from intimate confession in letters and journals to blog posts, tweets, and statuses, introducing verbal and structural experimental practices which involve shifting points of view.
Keywords: media; culture; realism; narrative; technology